Comment le dénier: legs de Melanie Klein - De Michele, Giustino (Bollettino Filosofico, 2021)
This contribution aims to localise and discuss Jacques Derrida’s elaboration of Melanie Klein’s work. This recognition draws on two early references (Of Grammatology, Writing and Difference), where Klein’s contributions to psychoanalysis are esteemed to open the way to a performative approach of the problem of the archi-trace, of generalised writing, and of a positive grammatology. Derrida would not inquire further on this path, at least explicitly. Nevertheless, his insistence on some motifs compatible with Klein’s heritage permits to retrieve her presence in two still unpublished seminars of his, belonging to the Politiques de l’amitié series: Manger l’autre (1989-90) and Rhétorique du cannibalisme (1990-91). Through Sigmund Freud’s positions on negation and on cannibalism, it will be possible to recognise the terms of Derrida’s reprise of those early references to Klein. Keywords: Archi-critère, Auto-hétéro-affection, Derrida, Grammatology, Trace